No major impact of new grape varieties on Bordeaux wine typicity: expert assessments in blind and non-blind tastings - Marc Plantevin; Sophie Tempère; Cécile Thibon; Lucile Dijkstra; Julien Lecourt; Agnès Destrac-Irvine; Cornelis van Leeuwen (OENO One)
Climate change induces major changes in wine typicity due to its impact on berry composition at harvest. This is of great concern for winegrowing regions historically renowned for their terroir and quality potential. Among different levers to adapt to climate change, the modification of grape varieties is considered to be very effective. However, this powerful tool can have repercussions for the protection of the region of origin’s wine typicity. In Bordeaux (France), a considerable research effort addresses the physiological traits of new varieties to thrive in a climate becoming increasingly dry and warm. Recently, a study investigating the typicity of 26 red varieties isolated five potential candidates (Fer Servadou, Duras, Manseng noir, Vinhão and Arinarnoa) sharing similar sensorial spaces compared to classical Bordeaux varieties. Varietal mix is strictly regulated by protected denomination of origin (PDO) rules, although these can change over time. If new varieties were to be accepted in the Bordeaux varietal mix, it would most likely be as secondary varieties accounting for a small proportion in the final Bordeaux blend. This study aimed to assess the impact of the five abovementioned varieties when incorporated into a classical Bordeaux blend (i.e., Cabernet-Sauvignon, Merlot, Cabernet franc and Petit Verdot), at a proportion of 10 % and 30 % respectively. Two sensory analysis tests were conducted within a two-month period. The first one, which included 37 professional judges, showed that Bordeaux wine typicity barely changed when these varieties were introduced at 10 % or 30 %, except for Vinhão that underwent a slight typicity decrease. The second sensory analysis test was conducted by 20 highly professional judges with an exceptional degree of expertise (> 15 years of experience), especially in blending. Assessing the wines through both blind and non-blind tastings (indication of the varieties present in the blend), the importance of the information on the typicity judgment was assessed. No significant differences were recorded between non-blind and blind tastings, showing that the perceptual judgement of the highly-experienced professionals was not influenced by the introduction of the new varieties to the classical blend. By means of ranking tests, this sensory analysis also showed that the Bordeaux reference blend was the most typical of the wines. Duras and Arinarnoa at 10 or 30 % had a non-significant effect on the blend’s typicity, while a significant decrease of typicity was observed when Fer Servadou (at 10 % or 30 %), Manseng noir (at 30 %) or Vinhão (at 30 %) were introduced to the Bordeaux reference blend. This shift of typicity only occurs, however, on a tight continuum of less to more typical wines.